2016
DOI: 10.1063/1.4944808
|View full text |Cite
|
Sign up to set email alerts
|

Cross-spectrum measurement of thermal-noise limited oscillators

Abstract: Abstract:Cross-spectrum analysis is a commonly-used technique for the detection of phase and amplitude noise of a signal in the presence of interfering noise. It extracts the desired correlated noise from two time series in the presence of uncorrelated interfering noise. Recently, we demonstrated that the phase-inversion (anti-correlation) effect due to AM noise leakage can cause complete or partial collapse of the cross-spectral function [1], [2]. In this paper, we discuss the newly discovered effect of anti-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…In spite of the discrepancy between the measurements and simulation, the relative differences in the measured thermal noise levels between 1-R and 3-R as well as between 3-R and 2-R power splitters are nearly the same as the simulated results. In [11], we demonstrated that if the power splitter is connected to a real 50 Ω load impedance, the simulation and experimental results agree well; we verified this for the AM noise measurements. The simulation results given in Table 1 for different types of power splitters were performed in the Advanced Design System (ADS) software.…”
Section: Cross-spectral Collapse Due To Power Splitterssupporting
confidence: 68%
See 2 more Smart Citations
“…In spite of the discrepancy between the measurements and simulation, the relative differences in the measured thermal noise levels between 1-R and 3-R as well as between 3-R and 2-R power splitters are nearly the same as the simulated results. In [11], we demonstrated that if the power splitter is connected to a real 50 Ω load impedance, the simulation and experimental results agree well; we verified this for the AM noise measurements. The simulation results given in Table 1 for different types of power splitters were performed in the Advanced Design System (ADS) software.…”
Section: Cross-spectral Collapse Due To Power Splitterssupporting
confidence: 68%
“…For this simulation, the thermal noise contribution of the source, the power splitter and the load resistors are considered. A detailed description of the simulation can be found in [11]. Table 1 tabulates the results of thermal noise contribution of the individual component to the output cross-spectrum as a fraction of the noise from R s .…”
Section: Cross-spectral Collapse Due To Power Splittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods). Thermal noise is intrinsically rejected in the cross-correlation process 25 Improvements to the close-to-carrier phase noise could be obtained with better ultra-stable laser frequency stability. Longer or cryogenic reference cavities 26,27 with crystalline coatings 28 or spectral hole burning stabilization 29 could lower the phase noise limit by one order of magnitude.…”
mentioning
confidence: 99%
“…In this conditions, the peak of {S yx } is close to zero, as predicted by Eq. (12). Off resonance, the resonator is open circuit (Γ = 1), hence its thermal noise does not appear in the signals x and y.…”
Section: First Experimentsmentioning
confidence: 99%